KONSTRUKSI METODOLOGIS TAFSĪR AYĀT AL-AḤKĀM MIN AL-QUR’AN AL-KARĪM KARYA ABIL FADHAL - Fatihatus Sakinah (AL ITQAN: Jurnal Studi Al-Qur'an, 2019)
This paper will discuss how Abil Fadhal's methodological construction in his Tafsīr Ayāt Al-Aḥkām Min Al-Qur'an Al-Karīm as a pioner work of interpretation with fiqh nuances in Indonesia. The lackness of fiqh studies with the study of tafsir Aḥkam is suggested as the factor that has resulted in efforts to verify the law through the main source the Islamic religion (al-Qur'an) becoming not very popular and still tightly closed. Abil Fadhal through his interpretation of Tafsīr Ayāt al-Aḥkām min Al-Qur'an al-Karīm then appeared and tried to break the tradition. As an Indonesian interpreter who was born in the contemporary era, he did not adhere to the model of tafsir that developed in Indonesia. Abil Fadhal chose to obey the principles of previous scholars who were considered more original, by making his interpretation of the asbāb al-nuzul history and hadiths ahkām and quoting the opinions of previous scholars. But, on the other side, the use of terms in accordance with the context of the locality and their concisepresentation (ijmāli) confirms the contemporary nuances in it.